A Model of Rhetorical Moves and Hedging Phrases for Writing Research Projects (Islas, 2026)
Introduction: The aim of this study is to analyze the rhetorical moves and the most recurrent hedging phrases characterizing the writing of research projects.Methods: By adopting a mixed-method approach, the authors compiled and processed seventeen research projects written by second-year students of the degree course English Language with a Second Foreign Language at Universidad Central ¨Marta Abreu¨ de Las Villas because of their relevance to their objectives and predetermined criteria of data selection.Results: The findings showed that three moves with corresponding steps and hedging phrases were consistently employed in the projects analyzed: Move 1: Establishing the territory (the situation), Move 2: Establishing a niche (the problem), and Move 3: Occupying the niche (the solution).Conclusions: The results provided valuable insights for improving the writing of research projects. Thus, the findings could contribute to enhancing the awareness of utilizing moves and steps, as well as hedging phrases when writing well-structured and coherent research projects.KEYWORDS: academic writing; hedging phrases; research projects; rhetorical moves
Keywords: Academic Writing; Hedging Phrases; Research Projects; Rhetorical Moves